Pengaruh Pengungkapan Biaya Lingkungan Terhadap Kinerja Keuangan Dengan Kinerja Lingkungan Sebagai Variabel Moderasi - Mahdy Ramadhana, Naufal; Angelina Setiawan, Mia (Universitas Negeri Padang, 2020)
The purpose of this research is to test empirically the effect of environmental cost disclosure on financial performance with environmental performance as a moderating variable. This research is a type of causative research. The data collection technique is literature study. Literature study is obtained from literature related to the problem to be studied. In this study, data were collected using the documentation method. The research sample was 36 manufacturing and mining companies listed on the Indonesia Stock Exchange, selected using the purposive sampling technique method, in which the population criteria were selected by companies listed in 2014, 2015, 2016, 2017 and 2018. SPSS version 22 was used to process data as well as test research hypothesis. This research found that disclosure of environmental costs has no effect on financial performance. Furthermore, environmental performance cannot moderate the effect of disclosure of environmental costs on financial performance